Lymphatic metastasis of papillary thyroid carcinoma: mechanism and clinicopathological physiology - Liu, Pu; Yu, Xianqiang (Frontiers in Endocrinology, 2026)
Lymphatic metastasis is a hallmark feature of papillary thyroid carcinoma (PTC), occurring in 30–80% of patients and significantly influencing clinical management. This review comprehensively examines the biological, anatomical, and clinical characteristics of lymphatic spread in PTC, focusing on its diagnostic and therapeutic implications. We detail the molecular mechanisms driving lymphangiogenesis, including the VEGF-C/VEGFR-3 axis and immune-evasion pathways, and highlight the distinct patterns of regional lymph node involvement—from central compartment (Level VI) to lateral (Levels II–V) and rare skip metastases. High-risk clinicopathological features, such as tumor size >2 cm, extrathyroidal extension, and aggressive histological variants, are discussed alongside molecular markers (BRAF V600E, TERT, RET/PTC) that predict metastatic potential. Management strategies are reviewed, balancing the benefits of prophylactic central neck dissection against its risks and emphasizing risk-adapted radioactive iodine therapy. Despite the frequency of lymphatic metastasis, its prognostic impact varies: microscopic nodal disease has minimal effect on survival, while macroscopic or extranodal extension increases recurrence and mortality risks. This synthesis of current evidence aims to guide clinicians in optimizing detection, treatment, and surveillance for PTC patients with lymphatic metastasis.